Potentialities and Challenges of Adopting English as a Medium Instruction at the Basic Level in Nepal - Bahadur Kadel , Purna (Pragyaratna प्रज्ञारत्न, 2024)
Nepal is a multilingual, multicultural, multireligious, and multi-diverse country which has 124 national languages and 142 ethnic groups. English as a medium of instruction (EMI) has been implemented in community schools since 2006 to catch up with the EMI policy of every country in the world. This study attempted to explore the potentialities and challenges of adopting EMI at school level and find out the reason behind adopting EMI in Nepal. The phenomenological research design has been adopted to address the research questions of this study. The sample of study was 8 teachers who were selected from four schools, at least 2 teachers from each school as respondents through purposive non-random sampling procedure. The findings of this study show the use of translanguaging in the EMI classroom, excessive motivation of parents and learners towards EMI, lack of teacher preparation, EMI with integration of digital pedagogy, and EMI as the main causes of the loss of of mother tongues in community schools. It is concluded that EMI is essential for the bright career of learners in the non-English speaking country like Nepal because of the excessive dominance of the English in every domain of human life. The English language has become the lingua franca and global language to open a gateway in business, trade, education, science and technology, information communication and technology, politics, media, and diplomacy.